Ammonium iodide-promoted unprecedented arylsulfonylation of quinone with sodium arylsulfinates. Issue 48 (30th November 2017) - Yuan, Jin-Wei; Liu, Shuai-Nan; Qu, Ling-Bo
Abstract: A novel ammonium iodide- promoted arylsulfonylation of quinones with sodium arylsulfinates has been explored. This reaction proceeded smoothly through unique nucleophilic addition reaction and produced the arylsulfonylation products in moderate to good yields. The reactions proceeded efficiently over a broad range of substrates with good regioselectivity and functional group tolerance. Graphical abstract: An efficient protocol for the synthesis of quinonyl arylsulfone derivatives has been developed via ammonium iodide- promoted arylsulfonylation of quinones with sodium arylsulfinates with moderated to good yields.